Wayang: Alternative Media for Teaching Ethnomathematics to Explore Students’ Creativity and Problem Solving - Afib Rulyansah; Dika Dwi Meilina (Universitas Nahdatul Ulama Surabaya, 2023)
Indonesia has a quite diverse local culture, one of which is wayang. Culture-based learning is very important to be implemented in Indonesia because of cultural diversity that can be used as learning media as well as cultural introduction to the nation's next generation. Can use ethnomathematics as a learning medium. Writing in this scientific article uses a qualitative descriptive methodology. The subjects of this study were fourth grade students. Where grade IV students were given a questionnaire about their knowledge related to wayang culture and were given math questions about flat shapes before and after treatment with ethnomathematics. Then the data is processed together with data during the action process and after the action with data analysis techniques to draw conclusions. The results show that from the previous 55% did not complete math problems, after the class action 85% of students experienced complete math problems on flat material. So that ethnomathematics can be used as a learning medium in elementary schools or MI (Madrasah Ibtidaiyah) and can also be used at the same time to introduce culture to the next generation of the nation.